Active control for machinery equipment induced structural vibration using H∞ criterion and PSO technique - Jian, Xu (Array, 2019)
In this paper, machinery equipment induced structural vibration was investigated and a composite system for structure and equipment was proposed. Tuned mass damper (TMD) and active tuned mass damper (ATMD) were respectively performed for vibration control, in addition, particle swarm optimization (PSO) was utilized for pursuing an optimal active control. Numerical results confirmed that the presented active control strategy could achieve a better vibration suppression compared to TMD control. The PSO based active control also gave inspiration for improving the traditional vibration control.